The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1192/bjp.113.499.593
|View full text |Cite
|
Sign up to set email alerts
|

Variations in II-Hydroxycorticosteroids in Depression and Manic-Depressive Psychosis

Abstract: Many instances of regular cyclic or periodic psychiatric and clinical syndromes have been reported (Richter, 1957). The duration of each cycle varies from 2 days to 18 months but is usually constant in a given subject and bears no relationship to external factors. Presumably they have their origin within the body, and a disturbance of endocrine function has been suggested in many cases. Some women show cycles corresponding to the menstrual rhythm, the abnormal phase preceding or accompanying the menstrual flow. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…However, the most acute fall in urinary excretion of urinary 11 OHCS occurred in the 'positive mood change' group between Day 1 and Day 3 after delivery, at the time that mood was rising. The change in 11 OHCS excretion in this group at the time of mood change is therefore in the direction predicted in studies of ECT and associated changes in mood and plasma 11 OHCS (Hullin et al 1967).…”
Section: Discussionsupporting
confidence: 64%
“…However, the most acute fall in urinary excretion of urinary 11 OHCS occurred in the 'positive mood change' group between Day 1 and Day 3 after delivery, at the time that mood was rising. The change in 11 OHCS excretion in this group at the time of mood change is therefore in the direction predicted in studies of ECT and associated changes in mood and plasma 11 OHCS (Hullin et al 1967).…”
Section: Discussionsupporting
confidence: 64%
“…The pattern in individual affective psychotics was markedly irregular, whereas in the other subgroups individual patterns were much the same as the mean of the subgroups. In particular, all five schizophrenics and four of the five patients in subgroup C showed a steep rise in 1 -OHCS levels to a marked peak at 06.00 hours, but only two of the six affective psychotics 24.00 12.00 psychotic before and Discussion Board et al (1956Board et al ( , 1957 reported raised plasma hydrocortisone levels in depressed patients in morning blood samples, as did Gibbons and McHugh (1962), Gibbons (1964), and Hullin et al (1967). Brooksbank and Coppen (1967), comparing morning (08.00-08.15 hours) and evening (21.00-21.15 hours) samples, considered that morning plasma 11-OHCS values were little above normal but that evening plasma concentrations were more closely related to the patients' clinical state.…”
Section: Resultsmentioning
confidence: 60%
“…2; and in another study we did not note any evidence of phase-shifting in samples taken at about 22.00 and 07.00 hours (Conroy et al, 1968). The tendency for plasma 11-OHCS levels to fall on clinical recovery (Gibbons and McHugh, 1962;Bridges and Jones, 1966;Hullin et al, 1967) is also illustrated in this patient. Here again this might not have been so clearly evident had serial samples not been taken.…”
mentioning
confidence: 64%